2020
DOI: 10.1111/jfpp.14474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of germination and high pressure treatments on brown rice flour rheological, pasting, textural, and structural properties

Abstract: Brown rice (BR) and brown rice germinated (GBR) for different times (0 hr, BR; 5 hr, GBR5; 9 hr, GBR9) were high pressure (HP) processed at 200–600 MPa for 10 min. Swelling, rheological, pasting and textural properties, and microstructural changes that are important in the cooking quality of BR flour were investigated. Germination and HP contributed to restricting swelling. The germination treatment induced more severe HP modifications. The 10 min treatment at 400 MPa was found to be the most desirable HP cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Among all, the saturated and unsaturated fatty acids specifically linoleic, oleic, and palmitic acids epitomized the major quantitative fraction in the brown rice cultivars. The outcomes are in complete agreement with several previous investigations that confirmed palmitic, oleic, and linoleic acid as the chief fatty acids in brown rice (Munarko et al, 2020; Wang et al, 2020). As per the evaluated fatty acid compositions of the brown rice cultivars, linolenic and oleic acids were found to be the dominant unsaturated fatty acids.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Among all, the saturated and unsaturated fatty acids specifically linoleic, oleic, and palmitic acids epitomized the major quantitative fraction in the brown rice cultivars. The outcomes are in complete agreement with several previous investigations that confirmed palmitic, oleic, and linoleic acid as the chief fatty acids in brown rice (Munarko et al, 2020; Wang et al, 2020). As per the evaluated fatty acid compositions of the brown rice cultivars, linolenic and oleic acids were found to be the dominant unsaturated fatty acids.…”
Section: Resultssupporting
confidence: 92%
“…Brown rice does not manifest wholesome proteins, but it contains all the indispensable amino acids vital for maintaining upright fitness and well‐being (Singh et al, 2021). Brown rice is a dehusked paddy that principally entails three sections, that is, 2%–3% embryo, 5%–6% bran, and 92% endosperm (Singh et al, 2018; Wang et al, 2020). Brown rice is nutritionally superior to that of the polished counterpart because it possesses intact bran layers that remain adhered to the kernel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, sensory features can be significantly modified after HHP-based combination treatment, thus contributing to develop novel food products with emerging or enhanced features. Regarding grains, combined germination and high pressure treatments have been reported to improve the rheological, pasting, textural, and structural properties of rice flour by adjusting the processing parameters ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although its consumption has an undeniable health-promoting effect, brown rice is not considered suitable as a staple food owing to its hard texture and not easy-tocook characteristic [5]. Germination is regarded as a domestic and economic strategy for reducing the difficulty of cooking as well as for improving the palatability of brown rice [6]. Moreover, targeted analyses have revealed that the germination process notably enhanced the concentration of nutrients and health-prompting compounds in brown rice.…”
Section: Introductionmentioning
confidence: 99%